Optimal placement of DSTATCOM using Artificial Bee Colony Algorithm - V.Tejaswini, Dr.D.Susitra (International Journal of Advanced Science and Technology, 2020)
Poor power quality problems are existed in distribution system because of more consumption of reactive power by the AC loads. DSTATCOM belongs to the family of custom power devices, which control reactive power flow effectively. Hence, a new swarm intelligent optimization i.e., Artificial bee colony algorithm (ABC) is implemented in this paper to identify the optimal location of DSTATCOM in radial distribution system. Main inspiration for artificial bee colony algorithm is intelligent foraging behavior of honey bees. Proposed artificial bee colony algorithm (ABC) is determining the optimal placing & sizing of D-STATCOM by solving power quality model. The solution encoded for minimization of Power loss & voltage stability index. The proposed algorithm is compared with traditional methods like GA, PSO & GWO in terms of convergence analysis.